Aminoacylation of tRNA 2′‐ or 3′‐hydroxyl by phosphoseryl‐ and pyrrolysyl‐tRNA synthetases. Issue 20 (8th September 2013) - Englert, Markus; Moses, Sarath; Hohn, Michael; Ling, Jiqiang; O‧Donoghue, Patrick; Söll, Dieter
Abstract : Class I and II aminoacyl‐tRNA synthetases (AARSs) attach amino acids to the 2′‐ and 3′‐OH of the tRNA terminal adenosine, respectively. One exception is phenylalanyl‐tRNA synthetase (PheRS), which belongs to Class II but attaches phenylalanine to the 2′‐OH. Here we show that two Class II AARSs, O ‐phosphoseryl‐ (SepRS) and pyrrolysyl‐tRNA (PylRS) synthetases, aminoacylate the 2′‐ and 3′‐OH, respectively. Structure‐based‐phylogenetic analysis reveals that SepRS is more closely related to PheRS than PylRS, suggesting that the idiosyncratic feature of 2′‐OH acylation evolved after the split between PheRS and PylRS. Our work completes the understanding of tRNA aminoacylation positions for the 22 natural AARSs. Abstract : O ‐Phosphoseryl‐tRNA synthetase aminoacylates the 2′‐OH of tRNA terminal adenosine. Pyrrolysyl‐tRNA synthetase aminoacylates the 3′‐OH of tRNA terminal adenosine. O ‐phosphoseryl‐tRNA synthetase resembles phenylalanyl‐tRNA synthetase.